Pengaruh Hedonic Shopping Motivation, Visual Merchandising, dan Store Atmosphere Terhadap Impulse Buying Melalui Positive Emotion Sebagai Variabel Intervening Pada Konsumen Industri Retail Tiongkok di Indonesia - Lutfiani, Izah; Farisi, Herdian; Yuliana, Ade (CV ODIS, 2023)
This research aims to analyze the impact of visual merchandising, store atmosphere, and hedonic shopping motivation on impulse buying, with positive emotion as a mediator for KKV Indonesia consumers. The research involved 120 respondents selected through purposive sampling. Data was collected through questionnaires and analyzed using the SEM-PLS method with the help of SmartPLS software. Based on the results, visual merchandising, store atmosphere, and hedonic shopping motivation significantly impact positive emotion. Positive emotion, in turn, has a significant effect on impulse buying. Positive emotion can act as a mediator in the relationship between visual merchandising, store atmosphere, hedonic shopping motivation, and impulse buying.